Strategic Factors that Influence Critical Thinking Ability in Mathematics Learning in Elementary Schools - Ningsih, Prapti Octavia; Harsono, Harsono; Wulandari, Murfiah Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
Mathematical critical thinking skills are a person's ability to understand the thought process in order to achieve rational thinking to do something or believe in what should be done. Many factors influence students' critical thinking abilities, including physical condition, motivation, intellectual development, anxiety and habits. This research aims to determine and analyze the factors that influence critical thinking abilities in mathematics learning. This type of research is quantitative research with a survey method. The population in this study were all fifth grade elementary school students in Kartasura District, taking 2 schools as research samples. The number of samples in this research was 200 students selected using purposive sampling technique. Data collection techniques in this research used instruments consisting of: (1) physical condition questionnaire, (2) motivation questionnaire, (3) anxiety questionnaire, (4) habits questionnaire, (5) intellectual development questionnaire and (6) thinking ability questionnaire critical. The data analysis used was Structural Equation Modeling (SEM) using the Smart AMOS 23 computer program. The results of this study showed that 1) physical condition and intellectual development had a significant effect on anxiety, 2) physical condition, motivation and intellectual development had a significant effect on habits, 3) habits and anxiety have a significant effect on critical thinking. Meanwhile, motivation has no significant effect on anxiety. Based on the research results, it can be seen that physical condition, motivation, intellectual development, anxiety and habits influence students' critical thinking abilities.